Review—Electrochemical Separation of Organic and Inorganic Contaminants in Wastewater. Issue 3 (1st March 2022) - Gao, Rui; Mosquera-Romero, Suanny; Ntagia, Eleftheria; Wang, Xiaofei; Rabaey, Korneel; Bonin, Luiza
Abstract : High energy input and chemicals additions are typically needed to deal with persistent pollutants, organic and inorganic, and organometallic complexes in wastewater. Particularly, organometallic complexes decrease the removal efficiency for other pollutants being treated with conventional technologies, which can lead to high operational costs and residues formation. The improperly treated wastewater contains nutrients (nitrogen and phosphorus), heavy metals, and persistent organics, which should be removed or recovered before discharging. Electrochemical technologies can achieve concomitant removal of persistent pollutants and resource recovery from wastewater, with the benefits of low chemical input, cost-effectiveness and reduced water consumption. In this review, we provide an overview of electrochemical technologies for the separation of organics and inorganics and their subsequent recovery. The focus is placed into electrodeposition, electrodialysis, membrane electrolysis, electrochemical oxidation, capacitive deionization, and bioelectrochemical systems. The main challenges considered at present are i) the cost and longevity of the materials, ii) the process efficiency and selectivity and iii) the complexity of the wastewater matrices. In this review it is projected that in the near future, the electrochemical separation and recovery of organics and inorganics will be preferred, as electrochemical cells powered by renewable energy can serve for decentralized and off-grid treatment approaches.